Studi Pendahuluan Penggunaan Media Pembelajaran Mind Map Pada Kemampuan Berpikir Kritis Anak Usia Dini Di TK Negeri 1 Labuapi - Annisa Failasufa; Gunawan Gunawan; Baik Nilawati Astini; Ika Rachmayani (Indonesian Publication Center, 2024)
This study aims to analyze the use of mind maps as a learning medium on the critical thinking skills of early childhood students. The research employed observation, interviews, and analysis of student work at TK Negeri 1 Labuapi. The results indicate that the use of mind maps as a learning medium has a positive impact on the critical thinking skills of early childhood students. This is evident in the increased ability of students to identify main ideas, connect information, and draw conclusions from the learning material. Mind maps help students visualize information and understand the relationships between concepts, making the learning process more enjoyable and interactive, and enhancing their critical thinking skills. Furthermore, the use of mind maps has also proven effective in fostering creativity and active participation among students in the learning process.